Transient inhibition of 53BP1 increases the frequency of targeted integration in human hematopoietic stem and progenitor cells - Ron Baik; M. Kyle Cromer; Steve E. Glenn; Christopher A. Vakulskas; Kay O. Chmielewski; Amanda M. Dudek; William N. Feist; Julia Klermund; Suzette Shipp; Toni Cathomen; Daniel P. Dever; Matthew H. Porteus (Nature Communications, 2024)
Abstract Genome editing by homology directed repair (HDR) is leveraged to precisely modify the genome of therapeutically relevant hematopoietic stem and progenitor cells (HSPCs). Here, we present a new approach to increasing the frequency of HDR in human HSPCs by the delivery of an inhibitor of 53BP1 (named “i53”) as a recombinant peptide. We show that the use of i53 peptide effectively increases the frequency of HDR-mediated genome editing at a variety of therapeutically relevant loci in HSPCs as well as other primary human cell types. We show that incorporating the use of i53 recombinant protein allows high frequencies of HDR while lowering the amounts of AAV6 needed by 8-fold. HDR edited HSPCs were capable of long-term and bi-lineage hematopoietic reconstitution in NSG mice, suggesting that i53 recombinant protein might be safely integrated into the standard CRISPR/AAV6-mediated genome editing protocol to gain greater numbers of edited cells for transplantation of clinically meaningful cell populations.